Pertumbuhan Ulin (Eusideroxylon zwageri Teijsm & Binn.) dari Beberapa Provenans Di KHDTK Samboja, Kalimantan Timur - Burhanuddin Adman; Mira Kumala Ningsih; Teguh Teguh; Zainal Arifin; Yustinus Iriyanto; Dwi Wahyu Mentari; Nanda Farhazakia (ULIN: Jurnal Hutan Tropis, 2021)
The high conservation status of ironwood (Eusideroxylon zwageri Teijsm & Binn.) causes conservation efforts need to be carried out immediately. Balitek KSDA has carried out ulin conservation efforts by building ulin ex-situ conservation plots in the Samboja KHDTK with seeds from the Sungai Wain, Sangatta and Berau. This study was conducted to evaluate the variation of ironwood plant growth from these three provenances in the Samboja KHDTK. The results showed that the average survival rate of ironwood plant was 79.12% and there were no differences in the three provenances. Plants from Sangatta have the best height and diameter growth compared to the Sungai Wain and Berau, which is 83.48 cm and 0.61 cm.